# Multiplying a constant and a linear monomial Online Quiz

#### Properties of Fluids

20 Lectures 4 hours

#### Thermal Properties of Matter

16 Lectures 2.5 hours

Following quiz provides Multiple Choice Questions (MCQs) related to Multiplying a constant and a linear monomial. You will have to read all the given answers and click over the correct answer. If you are not sure about the answer then you can check the answer using Show Answer button. You can use Next Quiz button to check new set of questions in the quiz. Q 1 - Simplify the expression shown:

6 × 8x

### Explanation

Step 1:

Simplifying

6 × 8x = 48x

Step 2:

So, 6 × 8x = 48x

Q 2 - Simplify the expression shown:

−12 × 9y

### Explanation

Step 1:

Simplifying

−12 × 9y = −108y

Step 2:

So, −12 × 9y = −108y

Q 3 - Simplify the expression shown:

7 × 13z

### Explanation

Step 1:

Simplifying

7 × 13z = 91z

Step 2:

So, 7 × 13z = 91z

Q 4 - Simplify the expression shown:

$\mathbf{\left ( \frac{1}{5} \right ) \times 9p}$

### Explanation

Step 1:

Simplifying

$\left ( \frac{1}{5} \right) \times 9p = \left ( \frac{9p}{5} \right)$

Step 2:

So, $\left ( \frac{1}{5} \right) \times 9p = \left ( \frac{9p}{5} \right)$

### Explanation

Step 1:

Simplifying

$\left ( \frac{−4}{11} \right) \times 9m = \left ( \frac{−36m}{11} \right)$

Step 2:

So, $\left ( \frac{−4}{11} \right) \times 9m = \left ( \frac{−36m}{11} \right)$

Q 6 - Simplify the expression shown:

−5 × (14n)

### Explanation

Step 1:

Simplifying

−5 × (14n) = −70n

Step 2:

So, −5 × (14n) = −70n

Q 7 - Simplify the expression shown:

$\mathbf{\left ( \frac{8}{3} \right ) \times \left ( \frac{3p}{4} \right )}$

### Explanation

Step 1:

Simplifying

$\left ( \frac{8}{3} \right ) \times \left ( \frac{3p}{4} \right ) = 2p$

Step 2:

So, $\left ( \frac{8}{3} \right ) \times \left ( \frac{3p}{4} \right ) = 2p$

### Explanation

Step 1:

Simplifying

$5 \times \left ( \frac{−4y}{15} \right ) = \left ( \frac{−4y}{3} \right )$

Step 2:

So, $5 \times \left ( \frac{−4y}{15} \right ) = \left ( \frac{−4y}{3} \right )$

### Explanation

Step 1:

Simplifying

$8 \times \left ( \frac{7x}{3} \right ) = \left ( \frac{56x}{3} \right )$

Step 2:

So, $8 \times \left ( \frac{7x}{3} \right ) = \left ( \frac{56x}{3} \right )$

Q 10 - Simplify the expression shown:

$\mathbf{\left ( \frac{-9}{15} \right ) \times (3z)}$

### Explanation

Step 1:

Simplifying

$\left ( \frac{-9}{15} \right ) \times (3z) = \left ( \frac{-9z}{5} \right )$

Step 2:

So, $\left ( \frac{-9}{15} \right ) \times (3z) = \left ( \frac{-9z}{5} \right )$

multiplying_constant_and_linear_monomial.htm